KERAGAMAN DAN ANALISIS KEKERABATAN Hoya spp. BERTIPE DAUN NON SUKULEN BERDASARKAN KARAKTER ANATOMI DAUN - Hakim, Aldi Rahman; Dorly, Dorly; Rahayu, Sri (Center for Plant Conservation Bogor Botanic Garden, Indonesian Institute of Sciences, 2013)
Hoya spp. (Apocynaceae: Asclepiadoideae) has differences in leaf type, there are succulent and non succulent leaf types. Anatomical structure of Hoya spp. leaf has not been widely studied, especially for the non succulent type. The aims of this research were to explore the diversity and relationship of non succulent Hoya, based on leaf anatomical characters represented by eight species i.e. H. bandaensis, H. campanulata, H. chlorantha, H. cilliata, H. coriacea, H. coronaria, H. densifolia and H. multiflora. Hoya leaf anatomical characters were observed on the paradermal and transversal section and analyzed by using IBM SPSS version 19 sotfware for cluster analysis. According to the paradermal observation, stomata were present at lower surface (hypostomatic) for all species, and amphistomatic (both surface) for H. densifolia. The type of stomata is cyclocytic for all species. Clustered stomata were found in H. coriacea. Observation on transversal section showed that all of species has the normal structure i.e cuticula, upper and lower epidermis, palisade parenchyma and spongy parenchyma with the variation in the layer thickness. The cluster analysis resulted four groups at distance scale 19. Each group has specific characters. The first group has trichomes on both sides of the leaf surface. The second group has amphistomatic stomatal. The third group has thin leaves. The fourth group has the widest stomata.